Establishment and maintenance of a persistent infection of L132 cells by human coronavirus strain 229E - Chaloner-Larsson, Gillian (Arch Virol, 1981)
A persistent infection by human coronavirus 229E (HCV/229E) was established in a human continuous cell line (L132). Following the initial infection with stock HCV/229E, several cultures were established of which two (HV1 and HV4) have been maintained by continuous passage for two years. These cultures have shed high titres of infectious virus continuously into the supernatant fluid since their initiation. The persistently infected cells were resistant to homologous super-infection but supported polio virus replication to normal titres. Preliminary tests indicated that 50–100 percent of the cells contain virus. Neither interferon nor reverse transcriptase could be detected in these cultures and the presence of defective interfering particles could not be demonstrated. VH1 and VH4 coronaviruses, isolated from these persistently infected cultures (HV) and identified by 229E antiserum neutralization, were more cytocidal than the parent virus as judged by plaque characteristics and CPE however, they were indistinguishable on the basis of density, EM morphology, and genome size. Present evidence indicates that temperature plays an important but as yet undetermined role in the establishment and maintenance of stable 229E persistently infected cell cultures.